Analysis of Grade 10 English Textbook with Reference to Curriculum and Examination - K.C., Laxman (Studies in ELT and Applied Linguistics, 2021)
This paper entitled “Analysis of Grade 10 English textbook with reference to curriculum and examination” was an attempt to explore the relationship among curriculum, text book and examination system. It aims to explore the contents in the textbook which were assumed by curriculum and evaluation procedures specified in the examination system. The contents and exposure sufficiency to develop intended language competency in learners were attempted to analyze. Another important concern of this paper was to explore the opinions of school level English teachers, who are the keys to materialize the textbook in relation to curriculum and examination system. Phenomenological research design was used in the study and the data was collected through interview, group discussion and interaction. The collected data were critically analyzed by developing themes. The findings of the study depict that there is insufficiency of the contents in the prescribed textbook for grade 10 in the experience of teachers and students. Similarly, they also noted that the contents are not suffice to achieve the objectives of the curriculum.